Optimizing Performance Asphalt Concrete Hot Rolled Sheet– Wearing Course (HRS-WC) Using Chitosan Powder - Jenny Caroline; Maritha Nilam Kusuma (U Karst, 2022)
Road quality is also affected by temperature and weather, leading to surface pavement deformation. It is necessary to improve the quality of the road pavement so that the quality of the road becomes more durable and stable. Hot Rolled Sheet – Wearing Course (HRS-WC) is flexible and has high durability. The natural mineral has been used as the filler for pavement construction. However, further research is necessary to obtain alternative and more sustainable materials. This study will discuss portland cement filler as a reference to compare filler replacement with chitosan powder (shellfish) based on the general specifications of the 2018 highway revision 3 division 6. Chitosan powder contains calcium oxide of 3.04% and silica oxide of 17.98%, which are similar to cement fillers. The composition of chitosan powder are 100%: 0%, 50%: 50%, 25%: 75%, and 0%: 100%. performance analysis is done through the marshall test. The results showed that the comparison of the use of the best chitosan powder was at the asphalt content of 7.3 with 50% : 50% with a marshall test value of 993.4 kg, flow 3.20 %, VMA 18.36%, VFB 72.01%, VIM 5.14, MQ 301.440 kg/mm. From the result which meets the requirement, the filler has shown quality improvement as an additional mixture according to (SNI 03-6723-2002). Hence still not optimal to replace portland cement because, from the value of the marshall test, portland cement has a higher marshall value than chitosan.